Price above all else: an analysis of expert opinion on the priority actions to scale up production and consumption of plant-based meat in Brazil - Newton, Peter; Eichhorst, Waverly; Hegwood, Margaret; Morais-da-Silva, Rodrigo Luiz; Heidemann, Marina Sucha; Hoffmann, Alexandre; Reis, Germano Glufke (Frontiers in Sustainable Food Systems, 2024)
Introduction Plant-based meats (PBM) are an emerging set of food technologies that could reduce the environmental impacts of food systems by mitigating consumer demand for animal products. However, scaling up the production and consumption of plant-based meats requires overcoming multiple technological, regulatory, political, and market barriers. An evidence-based prioritization of needs and actions may help actors (e.g., investors, funders, policymakers) who wish to help scale PBM achieve desired outcomes with limited resources. Research question What actions could most effectively help to scale up the production and/or consumption of plant-based meat in Brazil? Methods We selected Brazil as a case study of a country with a significant animal agriculture sector and a burgeoning PBM sector. We constructed a panel of nine experts and employed the Delphi technique during two rounds of an online survey to iteratively assess the degree of consensus and disagreement around the relative priority of 14 possible actions (identified from relevant literature) that could help to scale up the production and/or consumption of PBM in Brazil. We used the Importance, Neglect, and Tractability framework. Results The panelists collectively concluded that the top priority action for scaling up both the production and the consumption of plant-based meat in Brazil was to reduce the price of products for consumers. For most priority actions, there was greater consensus among panelists in the second round of the survey. Discussion Our findings contribute to an improved understanding of (a) which actions may be of highest priority for investors, funders, and policymakers, (b) synergies and differences between priority actions to scale up the production versus consumption of PBM in Brazil, (c) the relative merits of focusing on scaling up PBM production versus consumption, and (d) the strengths and limitations of assessing expert opinion on alternative protein futures using the Delphi technique.